Pandemi COVID-19 dan Pengangguran di Kabupaten Tangerang - Arini Hardjanto; Tanti Novianti; Dian Verawati Panjaitan; Sri Retno Wahyu Nugraheni; Sri Mulatsih (IPB University, 2022)
The economic performance of a country or region can be shown through various macro variables, including unemployment. The labor market is one part of the economic sector affected by the COVID-19 pandemic in addition to the health sector. Tangerang Regency is one of the region in Banten Province which is known as an industrial area and has a relatively large workforce. The purpose of this study is to analyze the effect of the COVID-19 pendemic on the open unemployment rate in Tangerang regency. This research method used are correlation analysis, Granger Causality and binary logistic regression model. Based on the results of the correlation analysis, it can be concluded that the district minimum wage (UMK) and the labor force have a significant and positive relationship with the unemployment rate and has moderate level of correlation, while based on the results of granger causality, it can be conclude that unemployment rate variable has a one way relationship with PDRB, UMK and the labor force. Variables that have a significant effect on reducing working hours during the pandemic are labor experience, experience squared, workings who work as argriculral, forestry, fisheries, operators and machine assembling workers, while the factors tha significantly affect the reduction in wages are labor status (married), age, age squared, profession (as manager, professional technician & assistant, service and sales personal, agricultural worker, forestry, fishery, processing worker, craft, machine operator and assembling, roug worker), essential sector and usage internet for work.